Differentiation and financial performance: a meta-analysis. Issue 5 (21st October 2019) - Mohammadi, Pegah; Fathi, Saeed; Kazemi, Ali
Abstract : Purpose: The purpose of this study is to meta-analytically compare the effect of differentiation strategy formulation on financial and non-financial performance to explore the agency problem. Design/methodology/approach: This study was conducted using a meta-analysis approach and CMA2 software. Hypotheses has been tested using cumulative effect sizes. Then, the cumulative effect sizes if some subsamples are also tested for robustness check by manipulation of circumstances. Findings: Based on the findings, differentiation affects performance dimensions. However, spite of shareholders' wealth maximization, differentiation has a smaller effect on financial performance (as the proxy of shareholders' wealth) compared with operational performance. Meanwhile, the robustness test showed that the results in all subcategories has also confirmed, and this supports the results. Research limitations/implications: The results catch attentions of shareholders to review the elements of management evaluation in the corporate governance system in a way that they focus more on stakeholders' interests in developing differentiation strategy. Limitations of this study is firstly based on limitations of meta-analysis approach, which provide general results of relevant studies so that the local conditions of each firm should be considered in deploying implications. Originality/value: Exploring the overall schema of firms (from past to present and in different research conditions) regarding the impact of differentiation strategy on performance has been the originality of this research because of potentials of meta-analysis against past field studies. This originality led to the discovery of the general confusion of firms in the development of differentiation strategy so that it emphasizes operational performance more than financial performance.